THE USE OF FIGURATIVE LANGUAGES FOUND IN PRODUCT ADVERTISEMENTS FOR DIFFERENT GENDERS - Willia Defisyani; Hamzah Hamzah; Fitrawati Fitrawati (English Language and Literature, 2018)
Figurative language is the use of words that make a reader have to make a good interpretation not only by seeing what the words refer to or what it is said on the text, but also by interpreting it from the context. Because of that, it can create a misinterpretation. The researcher used a descriptive method because the data were taken from the advertisements as documentation method. The data were collected by downloading the data, reading them repeatedly, identifying the data that consist of the figure of speech and putting them on table provided. The data were also analyzed by tabulating the data, categorizing the figurative language into different forms, interpreting the meaning, classifying them into different types of figurative language, and analyzing them based on theory of semantics, and language and gender so that misinterpretation cannot create. The results in this research are 3 types of figurative language found in product advertisements for different genders such as personification, simile, and hyperbole, and some differences of language between both genders such as the choice were of word, the vocabulary and the most significat types of figurative language which used by them.